A study of multiple high speed data networks and seamless vertical handoff for uninterrupted internet access to a hybrid network - Chowdhury, Shajib Roy; Pathan, Ashiq; Chowdhury, Shapath (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.